Application of Contrast‐Enhanced Ultrasound in the Diagnosis of Solid Pseudopapillary Tumors of the Pancreas: Imaging Findings Compared With Contrast‐Enhanced Computed Tomography. (9th June 2019) - Xu, Ming; Li, Xiao‐ju; Zhang, Xiao‐er; Pan, Fu‐shun; Tan, Yang; Huang, Tong‐yi; Hong, Yu; Huang, Guang‐liang; Xie, Xiao‐yan
Abstract : Objectives: The purpose of this study was to assess the characterization and usefulness of contrast‐enhanced ultrasound (CEUS) for diagnosing solid pseudopapillary tumors of the pancreas (SPTP) and compare the enhancement patterns with contrast‐enhanced computed tomography (CECT). Methods: Forty‐three SPTP lesions proved by pathologic findings in 42 patients examined with CEUS and CECT were included in this study. The enhancement characteristics and typical CEUS features of the tumors were investigated. These characteristics were compared according to lesion sizes. The enhancement patterns of CEUS were compared with CECT. Results: The most common enhancement levels of SPTP in the early phase and late phase for CEUS were isoenhancement (19 of 43 [44.2%]) and hypoenhancement (32 of 43 [74.4%]), respectively. The 4 most common enhancement patterns were hypo‐hypo (16 of 43 [37.2%]), iso‐iso (11 of 43 [25.6%]), hyper‐hypo (8 of 43 [18.6%]), and iso‐hypo (8 of 43 [18.6%]) enhancement. For the 43 SPTP lesions, typical CEUS features such as lesion membrane, intralesional vessel, and intralesional compartmentalization enhancements were detected in 30 (69.8%), 27 (62.8%), and 10 (23.2%) cases. Compared with CECT, isoenhancement during the early phase and hypoenhancement during the late phase were the most common imaging characteristics of CEUS. Conclusions: Lesion membrane, intralesional vessel, and intralesional compartmentalization enhancements are typical CEUS features of SPTP, especially for large lesions (lesion size ≥3.0 cm). Isoenhancement during the early phase and hypoenhancement during the late phase are the most common imaging characteristics of CEUS and CECT, making CEUS a viable alternative diagnostic method that is noninvasive.